2011
DOI: 10.1007/s00428-011-1088-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of stromal and vascular components of tonsillar polyps: high endothelial venules as participants of the polyp’s lymphoid tissue

Abstract: Tonsillar polyps are nonneoplastic lesions usually composed of variable amounts of lymphoid and vascular and connective tissues. All of them are generally assumed to be hamartomatous proliferations, but the profile of vascular and connective components has yet to be explored. The vascular system of the tonsils is complex and includes highly specialized structures (i.e., high endothelial venules (HEVs)) involved in lymphocyte homing into lymphoid tissues. In 14 tonsillar polyps and 26 control tonsils, an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This antibody recognizes a carbohydrate epitope expressed in high endothelial venules, specialized structures involved in lymphocyte homing into lymphoid tissues. 11 Lastly, immunohistochemical staining for fibronectin and collagens I and III revealed a decreased and disorganized distribution of these extracellular matrix proteins in lymphangiomas compared with normal tonsils. 11…”
Section: Histopathologymentioning
confidence: 90%
See 1 more Smart Citation
“…This antibody recognizes a carbohydrate epitope expressed in high endothelial venules, specialized structures involved in lymphocyte homing into lymphoid tissues. 11 Lastly, immunohistochemical staining for fibronectin and collagens I and III revealed a decreased and disorganized distribution of these extracellular matrix proteins in lymphangiomas compared with normal tonsils. 11…”
Section: Histopathologymentioning
confidence: 90%
“…16 Furthermore, a study of 14 cases of tonsillar lymphangioma found no gross evidence of lymphatic obstruction in the lesions or associated resected normal tonsils, even after serial sectioning of the tissue specimens. 11 This suggests that another mechanism is likely responsible for the pathogenesis of these tumors.…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, the tonsil is a less common site for the development of lymphangiomatous lesions. 2,3 The head and neck region is the most common site of lymphangiomatous lesions. Most arise in the skin and subcutaneous tissues, but other sites include the larynx, parotid gland, mouth, and tongue.…”
Section: Discussionmentioning
confidence: 99%
“…2 Of the 214 cases of orbital cavernous hemangioma referred to our center, none displayed any obvious inflammatory cells. 3 Recently, however, a case of orbital cavernous hemangioma that showed obvious inflammatory cell infiltration in the interstitium was presented at our center. The unique nature of this case, which is quite different from that of other typical orbital cavernous hemangiomas, prompted us to compile this case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation